2005
DOI: 10.1136/bmj.38338.674583.ae
|View full text |Cite
|
Sign up to set email alerts
|

Does home based medication review keep older people out of hospital? The HOMER randomised controlled trial

Abstract: Objective To determine whether home based medication review by pharmacists affects hospital readmission rates among older people. Design Randomised controlled trial. Setting Home based medication review after discharge from acute or community hospitals in Norfolk and Suffolk. Participants 872 patients aged over 80 recruited during an emergency admission (any cause) if returning to own home or warden controlled accommodation and taking two or more drugs daily on discharge. Intervention Two home visits by a phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
332
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(343 citation statements)
references
References 18 publications
6
332
3
2
Order By: Relevance
“…Several care transition programs have reported increased readmissions of up to 96 %: high-risk inpatients on a psychiatricsubstance abuse unit assigned to a peer mentorship intervention; 41 medically complex Veterans Affairs patients who received intensive primary care support; 42 younger general medicine patients assigned to nurse case managers coordinating outpatient care; 43 and patients with heart failure assigned to a comprehensive treatment program. 44 Explanations for these paradoxical findings included: increased receptiveness to inpatient treatment for long-standing psychiatric disorders; 41 improved provider-patient communication facilitating detection and treatment of undiagnosed medical problems; 4 2 patients better enabled to self-identify concerning symptoms and seek medical care; 42 personnel added to the care team increased complexity, impairing patients' ability to self-care; 45 and patients using the hospital as respite from housing or social problems. 7 Furthermore, other studies have demonstrated that increased outpatient contact (e.g., PN outreach) may be associated with more readmissions, particularly among younger low SES patients, 46,47 suggesting that such patients may need more finely targeted, and possibly more intensive, outpatient care.…”
Section: Discussionmentioning
confidence: 99%
“…Several care transition programs have reported increased readmissions of up to 96 %: high-risk inpatients on a psychiatricsubstance abuse unit assigned to a peer mentorship intervention; 41 medically complex Veterans Affairs patients who received intensive primary care support; 42 younger general medicine patients assigned to nurse case managers coordinating outpatient care; 43 and patients with heart failure assigned to a comprehensive treatment program. 44 Explanations for these paradoxical findings included: increased receptiveness to inpatient treatment for long-standing psychiatric disorders; 41 improved provider-patient communication facilitating detection and treatment of undiagnosed medical problems; 4 2 patients better enabled to self-identify concerning symptoms and seek medical care; 42 personnel added to the care team increased complexity, impairing patients' ability to self-care; 45 and patients using the hospital as respite from housing or social problems. 7 Furthermore, other studies have demonstrated that increased outpatient contact (e.g., PN outreach) may be associated with more readmissions, particularly among younger low SES patients, 46,47 suggesting that such patients may need more finely targeted, and possibly more intensive, outpatient care.…”
Section: Discussionmentioning
confidence: 99%
“…However, community pharmacy-based studies investigating medication management of home-dwelling elderly are rare. The already published pharmacy studies report on home-based medication reviews aimed at improving the appropriateness of prescribing (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…39 A more recent trial of nurse-led, home-based case management following discharge had no impact on readmissions. 40 Home visits by clinical pharmacists in one trial of 872 discharged patients 80 years or older, despite changes in management of 20% of participants, resulted in a 30% increase (P = 0.009) in readmissions, 41 whereas in another trial involving 362 medical patients, no impact on readmissions was noted. 42 One trial reported significantly reduced adverse drug events as a consequence of pharmacist counselling of patients following discharge but no change in readmissions.…”
Section: Post-discharge Home Visits or Telephonic Follow-upmentioning
confidence: 99%